2019
DOI: 10.1136/bmjopen-2018-025332
|View full text |Cite
|
Sign up to set email alerts
|

Can goal-setting for patients with multimorbidity improve outcomes in primary care? Cluster randomised feasibility trial

Abstract: IntroductionGoal-setting is recommended for patients with multimorbidity, but there is little evidence to support its use in general practice.ObjectiveTo assess the feasibility of goal-setting for patients with multimorbidity, before undertaking a definitive trial.Design and settingCluster-randomised controlled feasibility trial of goal-setting compared with control in six general practices.ParticipantsAdults with two or more long term health conditions and at risk of unplanned hospital admission.Interventions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 28 publications
3
45
0
Order By: Relevance
“…Their sociodemographic characteristics were similar to the population that attended each site. The magnitude of the change pre-post implementation was high, and greater than those reported by previous studies on guided care [26] or goal-setting interventions [27] for older adults with multimorbidity. Patients showed the lowest degree of satisfaction with care in the arrange dimension and the highest in the advise one.…”
Section: Discussionmentioning
confidence: 52%
“…Their sociodemographic characteristics were similar to the population that attended each site. The magnitude of the change pre-post implementation was high, and greater than those reported by previous studies on guided care [26] or goal-setting interventions [27] for older adults with multimorbidity. Patients showed the lowest degree of satisfaction with care in the arrange dimension and the highest in the advise one.…”
Section: Discussionmentioning
confidence: 52%
“…Thus, patients should be equipped with the right skillsets for self-care. Various studies identified the need to facilitate self-management and provide adequate support, for example, through community programmes [59][60][61][62][63][64][65][66]. Although healthcare providers might have provided self-management guidelines and support to polyclinic patients, our study found that patients' practices were still affected by their daily activities involving work and the community, as well as their beliefs and physical condition.…”
Section: Key Findings and Recommendationsmentioning
confidence: 65%
“…As such, patients should be equipped with the right skillset for self-care. Various studies identified the need to facilitate self-management and provide adequate support, for example through community programmes (55)(56)(57)(58)(59)(60)(61)(62). Even though healthcare providers might have provided self-management guidelines to polyclinic patients, our study found that patients' practices were also affected by their daily activities involving work and the community, as well as their beliefs and physical condition.…”
Section: Key Findings and Recommendationsmentioning
confidence: 65%